The Association of FLT3-ITD Gene Mutation with Bone Marrow Blast Cell Count,CD34, Cyclin D1, Bcl-xL and hENT1 Expression in Acute Myeloid Leukemia Patients - Paulus Budiono Notopuro, Paulus
Abstract Background & objective: FLT3-ITD has been recently used as a molecular prognostic marker for risk classification in acute myeloid leukemia (AML) therapy. In this study we aimed to investigate the association of FLT3-ITD gene mutation with bone marrow blast cell count, CD34 expression as malignant cell burden, cyclin D1 and Bcl-xL expressions as indexes of cell proliferation and anti-apoptosis and human equilibrative nucleoside transporter 1 (hENT1) expression as cytarabine transporter during AML treatment.